INFORMASI BIDANG EKONOMI DALAM ARTIKEL MAJALAH ILMIAH INDONESIA - Tambunan, Kamariah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2009)
The purpose of this study is to find out information of economic science in Indonesian learned periodicals. The samples are articles of FOKUS Bidang Ekonomi published on the period of 2006-2008. It consists of 3 volume of publications with 12 numbers mounted to 1082 articles. The result show that the year of published of journal articles are 2002-2007 and it was dominated by those published in 2005, comprised of 329 articles (30%). Those of them are financial economics, comprise of 355 articles (33%). The amount of single author is higher than the multiple ones (74%).